ESPÉCIES NÃO-NATIVAS DESESTABILIZAM A ASSEMBLEIA DE PEIXES EM RESERVATÓRIOS NEOTROPICAIS - Eichelberger, Ana Cristina Algeri (2018)
1. The stability of a community depends on its composition, richness and biological interactions, as well as the relationship of species with the environment. Invasive species negatively influence community stability and the strength and type of interactions may be related to community susceptibility to biological invasion. This is because non-native species are more likely to invade and settle in less stable communities. However, stability is not a directly measurable attribute in the community, and mathematical models have been developed to provide comparative parameters of community stability levels. 2. In this context, this study sought to evaluate whether non-native species cause instability in freshwater fish communities in Neotropical reservoirs. 3. The stability of the communities was measured using resilience and resistance metrics using the first order multivariate autoregressive model (MAR (1)), which were related to the wealth and abundance gradient (in number and biomass) of species of non-native fish. 4. The less stable reservoirs (less resilient and more reactive) were those with the highest abundance and abundance of non-native fish species. This was possibly because the structure of interactions between native species was modified, to some degree, with the introduction of a new species. Furthermore, we observed that this destabilizing effect became synergistic when more non-native fish species were added.